Generation of internal undular bores by transcritical flow over topography - Roger Grimshaw; D.H. Zhang; K.W. Chow (2006)
In both the ocean and the atmosphere, the interaction of a density stratified flow with topography can generate large-amplitude, horizontally propagating internal solitary waves. Often these waves appear as a wave-train, or undular bore. In this article we focus on the situation when the flow is critical, that is, the flow speed is close to that of a linear long wave mode. In the weakly nonlinear regime, this is modeled by the forced Korteweg de Vries equation. We will demonstrate how Whitham’s modulation theory may be applied to obtain an analytical description of undular bores, for flow over isolated obstacles and for flow over a step.